Broadband Quad-Element MIMO Antenna with Enhanced Isolation for Sub-6 GHz and Sub-7 GHz 5G Applications - Aung, Mya Sandar; Hla, Tin Tin (AI Society & STMIK Indonesia, 2024)
In this manuscript, a broadband quad-element MIMO antenna with enhanced isolation for n77, n78, and n79 bands of Sub-6 GHz and the n46 and n96 bands of Sub-7 GHz under 5G applications is designed. The designed antenna element is a rectangular monopole antenna comprising a semi-circular cut and a semi-circle embedded to obtain a wide bandwidth. These four-element antennas are aligned orthogonally to achieve the compact size and high isolation features of MIMO performance. The overall area of MIMO antenna is 40×40x1.6 mm3. MIMO antenna has a high isolation of <- 21 dB, an envelope correlation coefficient (ECC<0.002), a high diversity gain (DG> 9.99), an MEG gain of -3 dB, and a peak gain of 5.08 dBi.The results of the experiment are satisfactory with the S-parameter simulation results According to the results, a broadband quad-element MIMO antenna is a suitable candidate for Sub-6 GHz and Sub-7 GHz 5G applications.